2022
DOI: 10.1108/jes-06-2022-0364
|View full text |Cite
|
Sign up to set email alerts
|

A Russian carol: impact and dependence on global equity markets during the Ukraine invasion

Abstract: PurposeThe authors present a study of the short-term impact of the Russian–Ukrainian war on global equity returns. The study aims to show that the conflict was priced into markets and whether the intensity of the impact depends on economic factors, such as dependence on gas, or/and political factors, such as belonging to the former Soviet power circle.Design/methodology/approachUsing the event study and a sample of 77 capital markets, accounting for over 99% of global capitalisation, the authors apply a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Although the event's average impact is negative, the individual event reflects a heterogeneous impact on stock market returns. In another study, Ferrández Serrano and Angosto-Fernández (2022) reported a significant negative impact of the Russia–Ukraine war on market returns. Additionally, the authors highlighted the role of political and economic associations of countries with conflicting countries in their domestic market returns.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the event's average impact is negative, the individual event reflects a heterogeneous impact on stock market returns. In another study, Ferrández Serrano and Angosto-Fernández (2022) reported a significant negative impact of the Russia–Ukraine war on market returns. Additionally, the authors highlighted the role of political and economic associations of countries with conflicting countries in their domestic market returns.…”
Section: Literature Reviewmentioning
confidence: 94%
“…In recent years, several researchers have studied the impact of geopolitical conflicts such as war, border and trade disputes on the performance of stock markets (Boubaker et al, 2022;Ferr andez Serrano and Angosto-Fern andez, 2022;Gu et al, 2021;Hassan et al, 2022;Hudson and Urquhart, 2014;Kumari et al, 2022Kumari et al, , 2023Schneider and Troeger, 2006). For example, Kumari et al (2023) examined the impact of the Russian invasion of Ukraine in Feb 2022 on European stock market returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These results have also been confirmed by Boungou and Yati e (2022), where study has additionally noted that the afflictions regarding stock returns are more extensive in the countries neighboring Russia and Ukraine and the UN members opposing Russia's actions. Serrano and Angosto-Fern andez (2022) provided results for the impact of the Russia-Ukraine war on global equities. The study noted that by altering the investors' usual projections, such conflicts make the markets uncertain.…”
Section: Military Wars and Conflictsmentioning
confidence: 99%